2018
DOI: 10.1038/s41598-018-32756-w
|View full text |Cite
|
Sign up to set email alerts
|

A genosensor for detection of HTLV-I based on photoluminescence quenching of fluorescent carbon dots in presence of iron magnetic nanoparticle-capped Au

Abstract: Carbon dots and Fe3O4@Au were synthesized to develop a new biosensor to detect DNA target. We investigated the photoluminescence property of carbon dots (CDs) in the presence of Fe3O4-capped Au (Fe3O4@Au). Firstly, we designed two dedicated probes for unique long sequence region of human T-lymphotropic virus type 1 genome. One of the probes was covalently bound to the CDs. In the absence of target, CDs-probe was adsorbed on the surface of Fe3O4@Au through two possible mechanisms, leading to quenching the fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Another study that implemented the mechanism of fluorescence quenching was observed through the application of carbon dots (CDs) and iron magnetic nanoparticle-capped Au (Fe 3 O 4 @Au) [87]. In the study, Fe 3 O 4 @Au was used to adsorb the CDs on its surface.…”
Section: Fluorescence-based Assaymentioning
confidence: 99%
“…Another study that implemented the mechanism of fluorescence quenching was observed through the application of carbon dots (CDs) and iron magnetic nanoparticle-capped Au (Fe 3 O 4 @Au) [87]. In the study, Fe 3 O 4 @Au was used to adsorb the CDs on its surface.…”
Section: Fluorescence-based Assaymentioning
confidence: 99%
“…Ghobadi et al employed the photoluminescence method to immobilize the HTLV-1 Tax gene on the platform modified using carbon dots and Fe 3 O 4 -capped Au. The detection limit of HTLV-1 Tax DNA was found at 10 nM with a linear range of 10-320 nM [31]. In parallel work, this group fabricated a new platform to detect the 122-base segment of HTLV-1 Tax gene based on the graphene oxide (GO) and gold nanoparticles (AuNPs).…”
Section: Fluorescence Assays Based On Nanoparticlesmentioning
confidence: 99%
“…The detection limit of 15 fM and 5 fM were acquired from an ssDNA-CD-AuNPs complex and ssDNA-CD-AuNPs/GO assembly, respectively. Zarei-Ghobadi et al introduced a genosensor through quenching the CDs fluorescence in the attendance of Fe 3 O 4 -capped Au (Fe 3 O 4 @Au) for diagnosis of a special region of HTLV-1 genome [69]. Two dedicated probes were designed to diagnosis target DNA.…”
Section: Fluorescence Assays Based On Metallic Nanoparticles Nanoclusters and Nanosheetsmentioning
confidence: 99%
“…The higher photocurrent response of HTLV-1 DNA was observed than those of mismatch DNA, which confirmed that the constructed biosensor could efficiently discern various DNA sequences. The fabricated photoelectrochemical biosensor showed an ultrasensitive diagnosis of HTLV-1 [ 60] FRET between CDs and Fe 3 O 4 @Au NPs 10 nM 10-320 nM [69] CdTe QDs tagged complementary DNA probe 10 pg/ml 10 pg/ml -21 ng/ml [70] Hairpin shaped probe tagged with AG NCs 8.5 nM 10-200 nM [75] Photoelectrochemical Cascade photoactive materials and triple helix molecular switch 0.65 fM 1 fM -1 nM [115] DNA (11.3 aM). A PEC biosensor was fabricated by Wang et.al.…”
Section: Photoelectrochemical Detectionmentioning
confidence: 99%